2018
DOI: 10.1038/aps.2017.141
|View full text |Cite
|
Sign up to set email alerts
|

Inverse changes in plasma tetranectin and titin levels in patients with type 2 diabetes mellitus: a potential predictor of acute myocardial infarction?

Abstract: An early intervention using biomarkers to predict acute myocardial infarction (AMI) will effectively reduce global heart attack incidence, particularly among high-risk patients with type 2 diabetes mellitus (T2DM). This study attempted to identify potential biomarkers by detecting changes in the levels of plasma proteins in T2DM patients following onset of AMI in comparison with those without AMI. Volunteer T2DM patients without AMI (control; n=10) and T2DM patients with AMI (n=10) were recruited. Plasma sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…More recently, Yoshihisa et al reported that urinary N-terminal fragment (N-titin) of titin, a giant sarcomeric protein that is involved in muscular passive tension and viscoelasticity, could be a biomarker for predicting high risk dilated cardiomyopathy patients (6) by using the enzyme-linked immunosorbent assay (ELISA) system (7). In accordance with this finding, plasma titin is closely associated with the onset of acute myocardial infarction in patients with type 2 diabetes mellitus (8).…”
Section: Introductionsupporting
confidence: 62%
“…More recently, Yoshihisa et al reported that urinary N-terminal fragment (N-titin) of titin, a giant sarcomeric protein that is involved in muscular passive tension and viscoelasticity, could be a biomarker for predicting high risk dilated cardiomyopathy patients (6) by using the enzyme-linked immunosorbent assay (ELISA) system (7). In accordance with this finding, plasma titin is closely associated with the onset of acute myocardial infarction in patients with type 2 diabetes mellitus (8).…”
Section: Introductionsupporting
confidence: 62%
“…Twelve proteins among 23 were reported with acute inflammation, heart failure, thrombosis, and cardiac diseases . Transthyretin, hemoglobin subunit alpha, beta, antithrombin III, serum amyloid P‐component, fibrinogen α, ß, γ, alpha‐1‐acid glycoprotein 1 and 2, apolipoprotein A‐II, and serotransferrin are relatively highly abundant proteins in human serum and therefore already known biomarkers for cancer, inflammation, cardiac hypertrophy, and heart failure . Some proteins are known as muscle or cardiac muscle components, such as complement C‐4A, C3, obscurin, and titin …”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, this Special Issue of Acta Pharmacologica Sinica was planned to provide a forum for high quality original research and review articles to showcase the most recent advances in translational research and clinical practices on a wide-spectrum array of conventional as well as novel cardio-vascular biomarkers. Coverage of this Special Issue encompasses various forms of large or small molecules, such as proteins, peptides, cytokines, microRNAs, and metabolic by- This Special Issue covers a variety of pathological types of CVD, including acute myocardial infarction (AMI) [2][3][4][5] , heart failure [6] , aortic aneurysms [7,8] , carotid restenosis [9] , pulmonary arterial hypertension (PAH) [10] , and cardiac amyloidosis [11] . Several review articles provided in-depth analyses on the important diagnostic and prognostic roles of zinc [12] , oxylipins [13] , and leptin [14] in the fundamental cellular signaling and pathogenic processes in CVD and diabetes.…”
mentioning
confidence: 99%
“…Several review articles provided in-depth analyses on the important diagnostic and prognostic roles of zinc [12] , oxylipins [13] , and leptin [14] in the fundamental cellular signaling and pathogenic processes in CVD and diabetes. Notably, all the 7 original research articles are clinical research on Asian patients with AMI [5] or PAH [10] as well as European patients with AMI [2] , chronic heart failure [6] , vascular aneurysm [7] or restenosis [9] , and stroke [15] .…”
mentioning
confidence: 99%
See 1 more Smart Citation